BIM Development and Trends in Developing Countries: Case Studies - Rogers, J.; Chong, Heap Yih; Preece, C.; Lim, C. (Bentham Science, 2015)
The case studies in this book highlight the role of adequate BIM software techniques and the importance of governmental support in facing building challenges at the moment.